Structural imaging biomarkers for bipolar disorder: Meta‐analyses of whole‐brain voxel‐based morphometry studies. Issue 4 (26th November 2018) - Lu, Xin; Zhong, Yuan; Ma, Zijuan; Wu, Yun; Fox, Peter T.; Zhang, Ning; Wang, Chun
Abstract : Background: Bipolar disorder (BD) is a common and destructive psychiatric illness worldwide. Although it is known that BD is associated with morphological abnormalities of the brain, the regions implicated in BD remain unclear. Therefore, we aimed to update current knowledge on potential structural imaging biomarkers of BD. Methods: Studies published up to January 31, 2018, were identified by a comprehensive literature search of PubMed, EBSCO, and BrainMap voxel‐based morphometry (VBM) database. Whole‐brain VBM studies that examined gray matter (GM) abnormalities of group comparisons between BD and healthy controls (HC) and reported results as coordinates in a standard reference space were included. Different meta‐analyses were performed by activation likelihood estimation (ALE) algorithm. Results: A total of 46 studies with 56 experiments, including 1720 subjects and 268 foci were included. Seven different meta‐analyses were calculated separately across experiments reporting decreased or increased GM volume among BD, BDΙ, BD‐adults, and BD‐youths groups. Fifteen regions of significantly different GM volume between four groups and HC were identified. There were extensive GM deficits in the prefrontal and temporal cortex, and enlargements in the putamen, cingulate cortex, and precuneus. Conclusions: The results revealed that the thinning of prefrontal cortex was a key region in the pathophysiology of BD. The enlargement of the cingulate cortex may be implicated in a compensatory mechanism. It underscored important differences between BD‐adults and BD‐youths and specific biomarkers of three subgroups.